Students’ Perception toward ICT In English Learning - Isnaini Eddy Saputro (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The education system has been transformed to phenomena of education in the 21st century. The technology requires all the students to integrate with digital media that support the students and the teacher meeting virtually. This research used description qualitative to reveal students’ perception toward ICT in English learning by distributing the questionnaire by using Google platform to 26 students in one of Universities at Sorong City. Researcher used Likerts’ scale to count the percentage of students’ perception. There are 20 questions in questionnaire and most students agree that learning L2 by using ICT makes them enjoyable, cheerful, and self-confident, reduce students’ anxiety. They motivate to learn English through application because the applications help them to improve their cognitive in critical thinking, opinion and creativity, and creating material through technology. They use social media to learn English by watching the videos relating to English learning. To keep students’ positive perception toward ICT is hoped the English teacher using various applications in teaching process which is appropriate with English skills and English components. By teaching English using applications, it motivates students to learn more and the way to acquire the target language.